Prevalence and Severity of Dental Cavities in Adolescents - Leticia Espinosa González; Indira Gómez Capote; María de la Caridad Barciela González- Longoria; Rosa María González Ramos (Editorial Ciencias Médicas, 2024)
Introduction: Dental cavities is a multifactorial disease prevalent during childhood and adolescence. Objective: To determine the prevalence and severity of dental cavities in adolescents. Methods: A descriptive cross-sectional study was carried out in adolescents belonging to the Plaza de la Revolución municipality, Havana, Cuba, in the period from October 2019 to October 2022. The sample used was a stratified random sample of 969 adolescents. The COP-D was used to measure the prevalence of cavities, and the ICDAS system was used for severity and severity. The primary data were processed with Statistica 6.1 software. The chi-square test was performed with the Epidat program and the results were described by frequency and percentage figures. Results: The COP-D index was 1.92; in the group aged 18-19 years the COP-D was 1.96. In relation to cavities severity, 19.2% presented code 1 cavities; the 18-19 years age group showed 18.9% cavities involvement, related to the severity of the lesions; the highest percentages were presented in mild lesions with 35.2%. Conclusions: The prevalence of dental cavities was low. The rate of COP-D was slightly higher in the 18-19 years age group. In terms of severity, cavities code 1 and 2 lesions predominated; the highest proportions were mild.